National Safety Survey of Animal-use Commercial Probiotics and Their Spillover Effects From Farm to Humans: An Emerging Threat to Public Health. (12th July 2019) - Fu, Songzhe; Yang, Qian; He, Fenglan; Lan, Ruiting; Hao, Jingwei; Ni, Ping; Liu, Ying; Li, Ruijun
Abstract: Background: Human-use probiotics have recently been associated with clinical infections and antibiotic resistance transfer, raising public concern over their safety. However, despite their extensive application in aquaculture and animal husbandry, the safety of animal-use probiotics remains poorly described. Methods: We evaluated the safety of 92 animal-use probiotics from China. The pattern of spread of pathogens from probiotics and the consequent public health implications were also examined by conducting in-field genomic surveillance at 2 farms. Results: A total of 123 probiotic Bacillus species isolates were obtained from 92 brands of probiotics, of which 45 isolates were resistant to antibiotics. Notably, 33.7% of probiotic products were contaminated with life-threatening pathogens such as Klebsiella pneumoniae . Genomic surveillance at a chicken farm identified an anthrax toxin–positive Bacillus cereus strain in a probiotic product used as a feed supplement, which was transferred into the groundwater and to a nearby fish farm. Following up retrospective analysis of the surveillance data during 2015–2018 in 3 provinces retrieved 2 B. cereus strains from human with intestinal anthrax symptoms and confirmed the transmission of B. cereus from farm to human. Surveillance of anthrax toxin revealed that cya was detected in 8 of 31 farms. Conclusions: This study provides the first national safety survey of animal-use probiotics in China and confirms the spillover effects of probiotics from the farms to human. These results suggest that the large-scale application of pathogen-containing probiotics leads to the transfer of pathogens, with worrisome implications for public health. Good Manufacturing Practice should be implemented during the production of all probiotics. Animal-use probiotic products are frequently contaminated with viable pathogenic bacteria. This study revealed that virulent probiotic organisms and contaminating pathogens were colonized with farm animals and shed into the environment, which facilitated the transfer of pathogens to humans.